Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1080/00986449208935977
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Area Production at a Tee Junction

Abstract: Kerosene was dispersed in water at a tee junction. The Sauter mean droplet size was determined as a function of flow parameters. It is shown that significant differences exist between this system and others which have been reported. Some of these differences can be attributed to the hypothesis that the system has not achieved dynamic equilibrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They, along with Long (Long, 1983), discovered that the assumption of equilibrium for two-phase mixing systems is not always correct. Long and Reimus (Long, 1988a) and Long, et.al. (1992bLong, et.al.…”
Section: Calculating Interfacial Areamentioning
confidence: 94%
“…They, along with Long (Long, 1983), discovered that the assumption of equilibrium for two-phase mixing systems is not always correct. Long and Reimus (Long, 1988a) and Long, et.al. (1992bLong, et.al.…”
Section: Calculating Interfacial Areamentioning
confidence: 94%
“…They, along with Long (1983), discovered that assuming equilibrium for two-phase mixing systems is not always correct. Long and Reimus (Long et al 1988a(Long et al , b, 1992a and Long, Tavarez, Lin and Reimus (1992b) observed that Equations (2) and (3) do not fully account for the effects noted at a tee junction. In particular, they observed that Equations (2) and (3) must be corrected by additive terms that were proportional to dispersed phase volume fraction.…”
Section: Semi-empirical Modelsmentioning
confidence: 99%